Analysis of Economical and Environmental Costs for the Selection of Municipal Solid Waste Treatment and Disposal Scenarios through Multicriteria Analysis (ELECTRE Method) - Lorena De Medina-Salas (Sustainability, 2017)
Decision-making for the selection of treatment alternatives and landfilling of municipal solid waste (MSW) is based on the experience and judgment of those management responsible, without considering multicriteria analysis. Therefore, the purpose of this research was to determine the treatment scenario and landfilling of MSW with the lowest environmental and economic costs in a medium-sized city. The methodology included the definition and data processing of the project (population, generation, and composition of MSW), for 16 years. In the design of scenarios, recycling, composting, incineration with energy recovery, and landfilling treatments were proposed; later, the combinations of treatments for each type of residue were generated. The results showed 36 scenarios, then the ELECTRE method was applied to the five with the lowest economical and environmental costs. Finally from the latter, one dominant scenario was determined: organic waste in composting; plastic, paper, and glass in recycling; and ‘others’ in landfilling. It is concluded that the final decision on the scenario is adapted to the particular conditions of the locality.